Teleworking: its impact on workers in the city of Chillán, Chile (Encuentros, 2022)
Teleworking is a form of remote work performance in which the worker is not present in the company, using computer and telecommunication tools. As a result of the contingency due to the covid-19 pandemic, many companies found it necessary to implement it hastily and without measuring consequences. The objective of this study is to determine the impact teleworking has on workers as a result of the health crisis. A properly validated multiple-choice questionnaire was applied to 160 people and the selection was non-probabilistic, for convenience. It was divided into four sections. The first of them included the characterization of the respondents, the second referred to income, expenses and investments, the third included the reconciliation of work and family and, finally, the level of ICT knowledge that teleworkers had is included. The main conclusions are that they are unable to finish their work within their ordinary working hours, they do not reconcile work life with family life, which have increased their feeling of stress; and that Law 21,220 is not clear in terms of discriminating between the expenses of the company and those of the home
Keywords: Teleworking, Health crisis, disbursements for teleworking products